National trends in testing for hepatitis C virus in licensed opioid treatment programs: Differences by facility ownership and state medicaid expansion status. (1st November 2021) - Pro, George; Tompkins, D. Andrew; Azari, Soraya; Zaller, Nickolas
Abstract: Background: The recent surge in hepatitis C virus (HCV) prevalence is primarily due to increased injection drug use. Opioid treatment programs (OTPs) are a major source of treatment for people at risk for HCV and are ideal settings for on-site HCV testing. The purpose of this national study was to identify state- and facility-level factors associated with HCV testing availability. Methods: We used the National Survey of Substance Abuse Treatment Services (2019) to identify OTPs in the US ( n  = 1679). We used multilevel logistic regression to test for an association between HCV testing and state Medicaid expansion status, and assessed whether the association depended on private or non-profit OTP ownership, adjusted for state racial/ethnic minority populations, poverty, Medicaid access to HCV treatment, and HCV, opioid use disorder, and overdose rates. Results: Two-thirds of OTPs offered HCV testing. Medicaid expansion (versus non-expansion) was associated with a higher odds of HCV testing within OTPs owned by non-profits (adjusted odds ratio=1.99, 95% CI=1.02–3.91, p  = 0.04). Nearly all non-profit OTPs that were in expansion states had predicted probabilities that were higher than the national average. Conclusion: HCV testing was highest in non-profit OTPs in expansion states. This is concerning given the increasing dominance of private OTPs in the marketplace. Payment structures and reimbursement are likely factors driving the low rate of HCV testing in private facilities and could be addressed with health policies aimed at eliminating HCV. Expanding support for non-profit OTPs also has the potential to strengthen testing rates and improve health. Highlights: Hepatitis C virus prevalence has risen markedly in the past decade in the US. Strengthening HCV testing in opioid treatment programs could reduce disease burden. State demographic and treatment facility characteristics affect HCV testing availability. Medicaid expansion was positively associated with testing only among nonprofit OTPs. A sharp rise in private OTP ownership may pose a challenge to HCV elimination efforts.